Wine tourism among Generations X and Y - Getz, Donald (Array, 2008)
Summary: This paper examines the wine tourism experience from the perspective of young adults, specifically Generation X and Y consumers. Both the wine industry and wine tourism destinations have a particular interest in learning more about these age cohorts, as wine consumption and wine-related travel have been dominated by older adults. Little research has focused on Gen X and Y and how they might become more involved. Accordingly, in this paper their motivation for taking a winery tour, level of ego-involvement with wine, and how they got involved with wine in the first place are all assessed. Data were obtained using a self-completed questionnaire of customers of a wine tour company called Wine for Dudes that operates in Margaret River, Western Australia. These young wine tourists displayed a low level of ego-involvement with wine; they were mostly interested in learning about wine in a social context. The findings reinforces previous research indicating that many wine lovers (especially females and young consumers) are primarily interested in the hedonistic pleasure and social experiences associated with wine. The paper concludes with a theoretical discussion of how young wine consumers become involved with wine and wine tourism, including suggestions for further research